Understanding Indonesian Students’ Perceptions of Japan through One Piece as Cultural Diplomacy: The Case of Yogyakarta - Khofiyatul Awaliyah; Isti Nur Rahmahwati (Universitas Diponegoro, 2026)
As a popular culture, One Piece anime is strategically utilized in cultural diplomacy to enhance Japan’s global influence and image on the international level. One Piece is popular in Indonesia, especially among university students in Yogyakarta. This study examines how the cultural diplomacy of One Piece influences perceptions of Indonesian students in Yogyakarta towards Japan’s identity and cultural values. By using Alexander Wendt’s social constructivism, this study emphasizes the importance of social interaction in the construction of Japanese cultural identity, norms, and values through the cultural diplomacy of One Piece in Indonesia, supported by the Cool Japan policy. This study uses primary data collection through a survey of 150 students who are One Piece fans in Yogyakarta, as well as secondary data from various relevant documents. The survey is processed using SPSS. The result shows that the popularity of One Piece in Yogyakarta encourages the acceptance of values such as hard work, solidarity (friendship), and respect (bushido) that are typical of Japanese culture. It also proves that cultural diplomacy of One Piece contributes significantly to strengthening Japan’s positive image in Yogyakarta, Indonesia.